Natural Convection in a Representative Section of an ONAN Distribution Transformer - Córdoba Estrada, Paola Andrea (2017)
We present a 3D numerical modeling of an ONAN distribution transformer. We found that the 3D problem of natural convection in this thermohidraulic device can be studied by a numerical model that represents a 3D slice of an ONAN distribution transformer. The numerical study was carried out by applying the Finite Element Method to solve the 3D Navier-Stokes and heat equations using the in-house developed Par-GPFEP code. We compared the present results with those of other authors who used a similar approach with some differences in the solution method and in the simpliﬁcations considered. Also we compared the numerical temperature distribution with thermographies presented in a heating test performed in an ONAN transformer provided by Tubos Trans Electric S.A. The numerical results are also compared with velocity ﬁelds measurements taken in an experimental device that was built to simulate a representative slice of the transformer of interest. A PIV setup was used to obtain the ﬂow velocity ﬁeld. We found reasonable agreement between numerical and the preliminary experimental results, showing stratiﬁed temperature distributions and similar ﬂow patterns in the studied region.